PRINCIPALS RATING OF BUSINESS TEACHERS' EFFECTIVENESS IN PROFESSIONAL TEACHING COMPETENCIES IN AKWA IBOMSTATE, NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The need to ensure effective teaching of business subjects at the public secondary schoollevel inAkwa IbomState inspired thisstudy. Three researchquestionsguided the studyandanull hypothesis was tested at 0.05 level of significance. Descriptive survey research designwas used for the study. A population of 235 principals from all public secondary schools inthe area was studied without sampling because the size was manageable. An 18-itemquestionnaire with five response options was used for data collection. The instrumentwas validated by three experts. The reliability of the instrument was established usingCronbach Alpha correlation coefficient value of 0.87. Data collected were analyzed withmean for the research questions, and whilst student ttest was for testing the nullhypothesis. Findings of the study showed that business teachers are effective in thethree professional teaching competencies. It was also found that gender significantlyinfluenced the opinions of the respondents and the null hypothesis was rejected. It wasrecommended, among others, that: secondary school business subjects' teachers shouldattend short courses and conferences to update and upgrade their professional teachingcompetencies; and that government should adequately fund education for effectiveteaching of business subjects.